Between‐study differences in grip strength: a comparison of Norwegian and Russian adults aged 40-69 years - Rachel Cooper; Vladimir M. Shkolnikov; Alexander V. Kudryavtsev; Sofia Malyutina; Andrew Ryabikov; Laila Arnesdatter Hopstock; Jonas Johansson; Sarah Cook; David A. Leon; Bjørn Heine Strand (Wiley, 2021)
Abstract Background Identifying individuals with low grip strength is an initial step in many operational definitions of sarcopenia. As evidence indicates that contemporaneous Russian populations may have lower mean levels of grip strength than other populations in northern Europe, we aimed to: compare grip strength in Russian and Norwegian populations by age and sex; investigate whether height, body mass index, education, smoking status, alcohol use and health status explain observed differences and; examine implications for case‐finding low muscle strength. Methods We used harmonized cross‐sectional data on grip strength and covariates for participants aged 40-69 years from the Russian Know Your Heart study (KYH) (n = 3833) and the seventh survey of the Norwegian Tromsø Study (n = 5598). Maximum grip strength (kg) was assessed using the same protocol and device in both studies. Grip strength by age, sex and study was modelled using linear regression and between‐study differences were predicted from these models. Sex‐specific age‐standardized differences in grip strength and in prevalence of low muscle strength were estimated using the European population standard of 2013. Results Normal ranges of maximum grip strength in both studies combined were 33.8 to 67.0 kg in men and 18.7 to 40.1 kg in women. Mean grip strength was higher among Tromsø than KYH study participants and this difference did not vary markedly by age or sex. Adjustment for covariates, most notably height, attenuated between‐study differences but these differences were still evident at younger ages. For example, estimated between‐study differences in mean grip strength in fully adjusted models were 2.2 kg [95% confidence interval (CI) 1.4, 3.1] at 40 years and 1.0 kg (95% CI 0.5, 1.5) at 65 years in men (age × study interaction P = 0.09) and 1.1 kg (95% CI 0.4, 1.9) at age 40 years and −0.2 kg (95% CI −0.7, 0.3) at 65 years in women (age × study interaction P < 0.01). Conclusions We found between‐study differences in mean grip strength that are likely to translate into greater future risk of sarcopenia and poorer prospects of healthy ageing for Russian than Norwegian study participants. For example, the average Russian participant had a similar level of grip strength to a Norwegian participant 7 years older. Our findings suggest these differences may have their origins in childhood highlighting the need to consider interventions in early life to prevent sarcopenia.